The Concept of Religion-Science Integration: A Comparative Study of Naquib Al-Attas and Nidhal Guessoum - Fahmi, Muhammad; Soleh, Achmad Khudori; Cahyati, Lia (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
The integration of religion and science has garnered significant attention, as evidenced by the contributions of prominent Muslim thinkers such as Naquib Al-Attas, Ismail Al Faruqi, Mehdi Golshani, Ziauddin Sardar, and Nidhal Guessoum. This study aims to compare the perspectives of Naquib Al-Attas and Nidhal Guessoum regarding the integration of religion and science, using a literature review with a comparative descriptive approach and content analysis techniques. The findings reveal that Naquib Al-Attas’s concept of integration emphasizes three key aspects: a paradigm shift from Westernization to Islamization, a focus on language, and fostering ethical-moral values through ta’dīb. In contrast, Nidhal Guessoum highlights three distinct elements: the non-conflictual nature of science and religion, a layered interpretation of the Qur'an, and a theistic-falsification principle. The study identifies common ground between the two thinkers, including critical analysis of the origins of science, layered identification, and the incorporation of religious values. However, their differences lie in Naquib’s critique of the emergence of science versus Nidhal’s critique of the Islamization model, Naquib’s language-based approach versus Nidhal’s multilevel Qur'anic interpretation, and Naquib’s emphasis on Islamic ethics-morals versus Nidhal’s integration of sacred texts and reason under a theistic framework. The study concludes that Muslims should Islamize Western science by embedding ethical-moral ta’dīb, facilitating a harmonious dialectic between religion and science, wherein religion provides foundational values and science incorporates theistic principles.